INTEGRATION OF IOT TECHNOLOGIES IN THE WORKPLACE - Shukhratov Ma'mur Shukhrat ugli; Jumanazarov Javlon Shahnazar ugli (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The integration of IoT (Internet of Things) technology into the modern manufacturing environment provides enterprises with opportunities to optimize production processes, reduce energy consumption and improve product quality. This paper analyzes the application of IoT technology in manufacturing, its benefits and prospects for further development. It also provides information on how Internet of Things technologies are used by global companies and what innovative solutions are created on the basis of this technology. The article also discusses the main challenges and security issues faced when implementing Internet of Things technologies.